Orientational order of a ferroelectric liquid crystal with small layer contraction - PANOV, VITALI; FUKUDA, ATSUO; VIJ, JAGDISH (My University, 2010)
We present spectroscopic and optical studies of a non-layer-shrinkage ferroelectric liquid crystal DSiKN65. The orientational order parameters S, measured with respect to the smectic layer normal using IR spectroscopy on a sample aligned homeotropically, does not exhibit any significant variation between the smectic-A? and smectic-C? phases. In contrast the birefringence of a planar homogenous sample abruptly increases at the smectic-A? to smectic-C? transition. This suggests a general increase in the orientational order, which can be described by the orientational order parameters S? defined with respect to the director. Simultaneous increase of S? and the director tilt ? may explain the low shrinkage of smectic layers, which is consistent with recent theoretical models describing the smectic-A? to smectic-C? transition for such materials.
PUBLISHED
Keywords: Condensed matter physics; ferroelectric liquid crystal; DSiKN65; Nanoscience & Materials